The Yellow Coral Dendrophyllia cornigera in a Warming Ocean - Castellan, Giorgio; Angeletti, Lorenzo; Taviani, Marco; Montagna, Paolo (Frontiers in Marine Science, 2019)
Ocean warming is expected to impinge detrimentally on marine ecosystems worldwide up to impose extreme environmental conditions capable to potentially jeopardize the good ecological status of scleractinian coral reefs at shallow and bathyal depths. The integration of literature records with newly acquired Remotely Operated Vehicle data provides an overview of the geographic distribution of the temperate coral Dendrophyllia cornigera spanning the eastern Atlantic Ocean to the whole Mediterranean Sea. In addition, we extracted temperature values at each occurrence site to define the natural range of this coral, known to maintain its physiological processes even at 16°C. Our results document a temperature range between ~7-17°C, suggesting that the natural thermal tolerance of this eurybathic coral may represent an advantage for its survival in a progressively warming ocean.